2016
DOI: 10.3892/ol.2016.4706
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin induces apoptosis in human liver cancer HepG2 cells through extrinsic and intrinsic signaling pathways

Abstract: Abstract. Cordycepin, also termed 3'-deoxyadenosine, is a nucleoside analogue from Cordyceps sinensis and has been reported to demonstrate numerous biological and pharmacological properties. Our previous study illustrated that the anti-tumor effect of cordycepin may be associated with apoptosis. In the present study, the apoptotic effect of cordycepin on HepG2 cells was investigated using 4' ,6-diamidino-2-phenylindole, tetraethylbenzimidazolylcarbocyanine iodide and propidium iodide staining analysis and flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 36 publications
3
28
1
1
Order By: Relevance
“…Taken together, these data suggest that MRE could induce apoptosis of Hep3B cells through mitochondria- and Fas-mediated caspase-dependent pathways. These mechanisms have been reported previously using different agents to induce apoptosis of HCC cells [6769]. …”
Section: Discussionsupporting
confidence: 72%
“…Taken together, these data suggest that MRE could induce apoptosis of Hep3B cells through mitochondria- and Fas-mediated caspase-dependent pathways. These mechanisms have been reported previously using different agents to induce apoptosis of HCC cells [6769]. …”
Section: Discussionsupporting
confidence: 72%
“…It is know that changes in mitochondrial membrane permeability can cause the mitochondria mediated apoptosis signal pathway start [33,34]. However, our results showed that fluoride did not induce mitochondrial swelling of hepatocytes.…”
Section: Discussioncontrasting
confidence: 65%
“…Activation of multiple death receptors or the withdrawal of cytokines induces extrinsic pathway-mediated apoptosis [14,15]. Both the intrinsic and extrinsic pathways lead to the release of cytochrome C and other apoptosis-inducing factors, which subsequently activate downstream caspases [16]. …”
Section: Introductionmentioning
confidence: 99%